2016
DOI: 10.1007/s11858-016-0797-5
|View full text |Cite
|
Sign up to set email alerts
|

ICME international survey on teachers working and learning through collaboration: June 2016

Abstract: of those that did so reported explicitly on how their theoretical frame shaped the design of research methodologies/ approaches guiding activities with teachers. One significant outcome has been the difficulty of relating teachers' learning to collaboration within a project, although many initiatives report developments in teaching, teacher learning and students' learning.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
100
0
14

Year Published

2017
2017
2020
2020

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 97 publications
(124 citation statements)
references
References 88 publications
1
100
0
14
Order By: Relevance
“…The ways in which the participants in a PLC interact is closely linked to the roles they play within the community (Robutti et al 2016). The three elements of practice-engagement, imagination, and alignment of participant-can be employed as essential norms in a PLC (Jaworski 2003) for lesson study.…”
Section: Learning By Collaborative Work On Ttmmentioning
confidence: 99%
See 1 more Smart Citation
“…The ways in which the participants in a PLC interact is closely linked to the roles they play within the community (Robutti et al 2016). The three elements of practice-engagement, imagination, and alignment of participant-can be employed as essential norms in a PLC (Jaworski 2003) for lesson study.…”
Section: Learning By Collaborative Work On Ttmmentioning
confidence: 99%
“…Teacher researcher-or teacher-led inquiry communities have been increasingly viewed as promising for professional growth and development of theory and practice in mathematics education (Lin and Cooney 2001;Dowling 2013;Jaworski 2003;Slavit and Nelson 2010;Robutti et al 2016;Goodchild 2008;Goodchild et al 2013). Researchers have reported that teachers both deepen content knowledge and pedagogical knowledge by learning ways of teaching and develop their understanding of how to facilitate students' conceptual understanding through collaborative work with their colleagues and researchers (e.g., Sullivan et al 2012; K.-H. Lee (&) Seoul National University, Seoul, South Korea e-mail: khmath@snu.ac.kr Cooper et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Tanto la investigación como este artículo que focaliza en la propuesta, se conectan con cuestiones relativas a formación de futuros profesores en matemática. Esta área posee actualmente interés en el ámbito internacional (Even y Ball, 2009), señalamos los resultados del Survey presentado en el último Congreso Internacional de Educación Matemática (ICME) (Robutti, et al, 2016) y la convocatoria para la próxima Conferencia de Estudio número 25 (ICMI Study 25) a realizarse en febrero de 2020 (Borko, et al, 2019). A su vez, la preocupación respecto a la formación matemática de jóvenes de los distintos niveles educativos pone de manifiesto la necesidad de contribuir y prestar especial atención a la formación docente de quienes enseñarán matemática.…”
Section: Introductionunclassified
“…Teacher researcher-or teacher-led inquiry communities have been increasingly viewed as promising for professional growth and development of theory and practice in mathematics education (Lin and Cooney 2001;Dowling 2013;Jaworski 2003;Slavit and Nelson 2010;Robutti et al 2016;Goodchild 2008;Goodchild et al 2013). Researchers have reported that teachers both deepen content knowledge and pedagogical knowledge by learning ways of teaching and develop their understanding of how to facilitate students' conceptual understanding through collaborative work with their colleagues and researchers (e.g., Sullivan et al 2012 Cooper et al 2006).…”
Section: Introductionmentioning
confidence: 99%